2021
DOI: 10.1186/s12911-021-01446-5
|View full text |Cite
|
Sign up to set email alerts
|

Implications for the design of a Diagnostic Decision Support System (DDSS) to reduce time and cost to diagnosis in paediatric shoulder instability

Abstract: Background Currently the diagnosis of shoulder instability, particularly in children, is difficult and can take time. These diagnostic delays can lead to poorer outcome and long-term complications. A Diagnostic Decision Support System (DDSS) has the potential to reduce time to diagnosis and improve outcomes for patients. The aim of this study was to develop a concept map for a future DDSS in shoulder instability. Methods A modified nominal focus gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Shoulder instability is a complex phenomenon with poorly understood mechanisms. 18 This is particularly true for people with FSHD where the mechanism for shoulder instability may be different as a result of the changes to either the biomechanics (eg, properties of the musculoskeletal architecture/tendon) or the neural control (eg, recruitment of motor units) of the musculoskeletal system associated with the condition. 19 The aforementioned impairments relating to biomechanics and neural control may be assessed using imaging such as MRI and 3D movement analysis in combination with electromyography, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoulder instability is a complex phenomenon with poorly understood mechanisms. 18 This is particularly true for people with FSHD where the mechanism for shoulder instability may be different as a result of the changes to either the biomechanics (eg, properties of the musculoskeletal architecture/tendon) or the neural control (eg, recruitment of motor units) of the musculoskeletal system associated with the condition. 19 The aforementioned impairments relating to biomechanics and neural control may be assessed using imaging such as MRI and 3D movement analysis in combination with electromyography, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Responses of people with FSHD were supportive of MRI, which may provide further insight into mechanisms of shoulder instability in FSHD and inform upper limb rehabilitation. 18 Of the people who exercised, a broad range of exercise modalities were identified, and many participants suggested that they also seek support outside of their immediate care team. Although variability in exercise selection may be reflective of the heterogeneity within this patient group, our study suggests that the variability may reflect the lack of evidence-based guidelines for FSHD and how exercise interacts with it.…”
Section: Discussionmentioning
confidence: 99%
“…Authors in [8] developed a DDSS for the assessment of diabetic neuropathy using fuzzy approach, which is a nice sample of a successful DDSS. They obtained 93% accuracy in detecting motors, perceptual, combined neuropathies, and usual cases using data input that included indications and medical test results when contrasted to specialists.…”
Section: Diagnostics Supportmentioning
confidence: 99%
“…Whilst significant demonstrable benefits, such as decreasing unnecessary surgery or reducing cost to the service or a patient, may be the main driver for the adoption of this technology, it is also likely that the logistical and operational challenges associated with using this technology limit its overall clinical applicability for some patient groups ( Philp et al, 2021 ). Camera-based, 3D analysis is reliant on specialist technical skills and processes regarding capture, reporting and interpretation of data which are time consuming and resource intensive.…”
Section: Introductionmentioning
confidence: 99%